Successful treatment of Corynebacterium urealyticum encrusting cystitis with systemic and intravesical antimicrobial therapy - Raab, Oriana (Can Vet J, 2015)
A 6-year-old Saint Bernard dog was diagnosed with encrusting cystitis caused by Corynebacterium urealyticum. The infection persisted despite the prolonged use of antimicrobials and surgical debridement of the urinary bladder. Resolution occurred following intravenous vancomycin, urine acidification, and intravesical gentamicin. The challenges involved in the treatment of encrusting cystitis are described.